Controllable Sliding Transfer of Wafer‐Size Graphene. Issue 9 (15th March 2016) - Lu, Wenjing; Zeng, Mengqi; Li, Xuesong; Wang, Jiao; Tan, Lifang; Shao, Miaomiao; Han, Jiangli; Wang, Sheng; Yue, Shuanglin; Zhang, Tao; Hu, Xuebo; Mendes, Rafael G.; et al.
Abstract : The innovative design of sliding transfer based on a liquid substrate can succinctly transfer high‐quality, wafer‐size, and contamination‐free graphene within a few seconds. Moreover, it can be extended to transfer other 2D materials. The efficient sliding transfer approach can obtain high‐quality and large‐area graphene for fundamental research and industrial applications.